Roles of specialist intensive care nurses in mechanical ventilation - Ladipo, Chinwe Jacinta (My University, 2017)
The purpose of this study was to describe the role of specialist nurses in mechanical ventilation management. The intention of the study was also to make recommendations for clinical practice and education of intensive care nurses. The setting of the study was ten (n = 10) adult intensive care units of two public hospitals in the Gauteng province. Included were trauma ICUs, cardiothoracic ICU, coronary care ICUs, major burns ICU, major injuries ICU, neurosurgery ICU and multidisciplinary ICUs. A non-experimental, descriptive, quantitative and cross-sectional survey design was used to describe the specialist nurses role in ventilation management. The final sample comprised 110 (out of 165) respondents, which yielded a response rate of 66.6% for the study. Data were collected from specialist intensive care nurses using a validated questionnaire developed by Rose et al. (2011). Data was analysed using descriptive (frequencies, means and standard deviation) and comparative statistical tests using t-tests and Chi-square analysis. Testing was done at the 0.05 level of significance. Of the 165 surveys distributed, 110 were returned (response rate 66.6%). Ninety-seven percent stated that a 1:1 ratio was used for patients receiving mechanical ventilation. Eighty-nine percent reported ventilation education for nurses was provided during ICU orientation, and 86.4% indicated ICUs provided opportunities for on-going ventilation education. Eighty-six percent of nurses reported that they had not worked in ICUs with automated weaning modes. Fifty-nine percent stated that weaning protocols were present in ICUs, and 56.4% reported the presence of protocols for weaning failure. Most nurses agreed that nurses and doctors collaborated in key ventilation decisions, but not when decisions to extubate and initial ventilation settings are made. This study showed a marginal (2%) number of nursing autonomous input made in key ventilator decisions. Seventy percent of nurses in this study agreed that responsibility for ventilation decisions lies at the level of senior registrars and above, and in their absence, only senior nurses (>80%) were perceived to be responsible for key ventilator decisions. Regarding independent titrations of ventilator settings, without medical consultation, findings showed that nurses in this study reported a frequency of >50% of the time for titration of respiratory rate, tidal volume, decreasing pressure support, increasing pressure support, titration of inspiratory pressure and ventilation mode changes. The self-perceived nursing autonomy and influence in decision making revealed a median score of 7 out of 10 points, respectively. Nurses with higher levels of autonomy, influence in decision making and years of experience scores, frequently (>50% of the time) made independent changes to ventilation settings (p<0.05). Conversely, nurses with fewer years of experience scores, infrequently (<50% of the time) made independent changes to ventilation settings without first checking with the doctor. The study concludes that nurses to re-evaluate their role in ventilation management and focus on key ventilation settings, nurses could strengthen their contribution in the collaboration of key ventilator settings. Recommendations are made for clinical practice and education of specialist nurses.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2017
Keywords: Specialist Nurses; Respiration, Artificial (Mechanical Ventilation); Intensive Care Units